Monkeypox Transmission, Need and Treatment of Humans with an Antiviral Drug - Jabeen, Chanda; Umbreen, Gulshan (International Journal of Social Sciences and Management, 2017)
Monkeypox is a viral zoonotic disease belongs to the family Poxviridae and Orthopoxvirus genus. Transmission of monkey pox is through direct contact with infected animal and blood. Human to human transmission occur through respiratory route but previously so many studies are conducted to prove that monkey pox viruse was not transmitted through the respiratory route both in animals and humans. But now monkey pox is able to survive in humans due to genetic changes and human to human transmission is possible. Because it can be used as bioweapon, So there is a great need of having an antiviral drug which is effective against monkey pox virus.ST 246 proved effective in vivo and in vitro in infected animals and trials done safely on non-infected humans but no data is available about the effectiveness of ST 246 on monkey pox or Orthopox infected human treated with ST 246. Int. J. Soc. Sc. Manage. Vol. 4, Issue-2: 77-79